Pengaruh Tekanan, Kesempatan, Rasionalisasi, dan Kemampuan terhadap Kecurangan Laporan Keuangan: Studi Empiris pada BUMN yang Terdaftar di BEI - Annisa Nurul Izzati; Efrizal Syofyan (Universitas Negeri Padang, 2026)
This research aims to investigate the effects of elements of diamond fraud (pressure, opportunity, rationalization, and capability) on detected cases of fraudulent financial reporting. The study provides insights into the influence of pressure, proxied by financial stability, external pressure, and financial targets; opportunity, proxied by the nature of the industry; rationalization, proxied by changes in auditors; and capability, proxied by changes in directors. The analysis was conducted using multiple linear regression on a dataset of 60 samples BUMN listed on the Indonesia Stock Exchange during the period 2018-2020. The results indicated an R2 value of 0.829 or 82.9%, suggesting that pressure, opportunity, rationalization, and capability accounted for 82.9% of the variance, while the remaining 17.1% was attributed to other variables outside the scope of this research. The findings revealed that the financial target variable had a significantly positive effect on fraudulent financial reporting, while external pressure and changes in auditors had a significantly negative impact. Financial stability, the nature of the industry, and changes in directors showed no significant effects on fraudulent financial statements.